2009
DOI: 10.1128/jb.00185-09
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Cues Control Pseudomonas aeruginosa Multicellular Behavior in Cystic Fibrosis Sputum

Abstract: Volume 189, no. 22, p. 8079-8087, 2007. Page 8080, column 1, fifth paragraph, second and third lines, the parenthetical expression should read as follows: "(6.5 ml 0.2 M NaH 2 PO 4 , 6.25 ml 0.2 M Na 2 HPO 4 , 0.348 ml 1 M KNO 3 , 1.084 ml 0.25 M K 2 SO 4 , 0.122 g NH 4 Cl, 1.114 g KCl, 3.03 g NaCl, 10 mM MOPS, 779.6 ml deionized water)." 2906 on May 12, 2018 by guest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
200
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(210 citation statements)
references
References 0 publications
10
200
0
Order By: Relevance
“…For example, synergistic and antagonistic behavior between different CF pathogens has been described (Duan et al, 2003;Harrison, 2007;Sibley et al, 2008;Mitchell et al, 2010;Yang et al, 2011;Venkataraman et al, 2014), and the microbial community has been proposed to contain stable and disturbed states, much like those in classical ecology (Conrad et al, 2012). Known chemical characteristics of the CF lung include lowered pH (Tate et al, 2002;Pezzulo et al, 2012), low oxygen tensions (Worlitzsch et al, 2002) and high levels of amino acids, nitrate, iron and phenazines (Grasemann et al, 1998;Jones et al, 2000;Palmer et al, 2007;Ghio et al, 2012;Hunter et al, 2012). In the environment, microbial communities are known to stratify based on oxygen and other chemical gradients (Fenchel and Finlay, 2008;Morris and Schmidt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, synergistic and antagonistic behavior between different CF pathogens has been described (Duan et al, 2003;Harrison, 2007;Sibley et al, 2008;Mitchell et al, 2010;Yang et al, 2011;Venkataraman et al, 2014), and the microbial community has been proposed to contain stable and disturbed states, much like those in classical ecology (Conrad et al, 2012). Known chemical characteristics of the CF lung include lowered pH (Tate et al, 2002;Pezzulo et al, 2012), low oxygen tensions (Worlitzsch et al, 2002) and high levels of amino acids, nitrate, iron and phenazines (Grasemann et al, 1998;Jones et al, 2000;Palmer et al, 2007;Ghio et al, 2012;Hunter et al, 2012). In the environment, microbial communities are known to stratify based on oxygen and other chemical gradients (Fenchel and Finlay, 2008;Morris and Schmidt, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst a dry-powder preparation of mannitol is an approved osmolyte therapy for use in CF patients, it is important to exercise caution when considering the clinical significance of the present study, as clearly the nutritional cues present in the CF airways are not equivalent to those present in MYEM. We have observed that supplementation of synthetic CF sputum medium (SCFM; Palmer et al, 2007) with mannitol supports EPS biosynthesis (C. Denman & A. Brown, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa strains that initiate infections in CF can produce a huge arsenal of metabolic and virulence factors [16], can use the nutrients in the lung to promote growth [52] and can synthesize many toxic factors, such as pyocyanin, a type III secretion system, a variety of proteases, lipases and phospholipases, rhamnolipids and other potentially toxic factors [16,21,53]. Another key change in the organism associated with virulence in the CF lung is the loss of synthesis of the LPSO side chain [54] combined with the synthesis of the lipid A component as an isoform more likely to promote inflammation [55].…”
Section: Establishment Of Chronic Infectionmentioning
confidence: 99%